An Experimental Investigation on the Effect of Injection Pressure on the Exhaust Emissions of a Diesel Engine Fueled with Methanol-diesel Blends - SAYIN, CENK (TAYLOR & FRANCIS INC, 2011)
In this study, the effect of injection pressure on exhaust emissions of a diesel engine using methanol blended diesel fuel from 0 to 15% was investigated. A four-stroke, single-cylinder, naturally aspirated, direct-injection diesel engine was used for conducting this study. The original injection pressure of the engine is 200 bar. The tests were performed at three different injection pressures (180, 200, and 220 bar) by changing the injector spring tension. According to the test results, Bsfc and the emissions of NOx and CO2 increased as the emissions of smoke, CO, and unburned hydrocarbon decreased with an increasing amount of methanol in the fuel mixture. In addition, high injection pressure for smoke opacity, CO, and unburned hydrocarbon; low injection pressure for NOx; and CO2 must be preferred for decreasing emissions. In terms of Bsfc, the best results were obtained at 200 bar injection pressure for all engine loads.
Keywords: diesel engine; diesel fuel; emissions; injection pressure; methanol; FRYING PALM OIL; COMBUSTION CHARACTERISTICS; PERFORMANCE; BIODIESEL